(untitled) (Journal of Engineering, 2024)
This study focuses on the simulation of the bed change and total sediment concentration in the Al-Musayyab Canal, which is a vital irrigation system located in the central region of Iraq, using HEC-RAS V 6.3 software. The 49.5 km canal, with 13 branches, faces challenges from sediment influx originating from the Euphrates River. The primary objective is to analyze sedimentation, erosion patterns, and sediment discharge variations to support effective canal management. Field sampling collected suspended and bed load samples for laboratory tests, providing input data for the sediment transport model. Simulation results show steady flow water surface elevations ranging from 26.32 to 33.16 m.a.s.l, with velocities from 0.24 to 0.98 m/s. Significant sediment deposition and erosion variations are observed as data for 2019 and 2020 are analyzed. Notable changes in the canal’s invert levels occurred in both years, with maximum deposition depths reaching 14 cm in 2019 and 21 cm in 2020. Erosion depths ranged from 3 to 15 cm in 2019 and 5 to 25 cm in 2020. The total sediment discharge for 2019 in the Al-Musayyab Canal amounted to 17 tons/day, while 22 tons/day in 2020.